Configuration synthesis of variable stiffness mechanisms based on guide-bar mechanisms with length-adjustable links. (February 2021) - Shao, Yixin; Zhang, Wuxiang; Ding, Xilun
Highlights: A new configuration synthesis method to design variable stiffness mechanisms. The variation of the stiffness is achieved by adopting length-adjustable link. The conditions for designing variable stiffness mechanisms are derived. Variable stiffness mechanisms with different stiffness performance are constructed. The concept design of an energy-efficient variable stiffness actuator is shown. Abstract: A variable stiffness mechanism (VSM) is used to connect the principal motor and the load of a serial-configuration variable stiffness actuator (VSA) and can adjust the intrinsic stiffness of the VSA to improve the dynamic performance, energy efficiency, and safety of robotic systems. This paper presents a new configuration synthesis method to design VSMs based on guide-bar mechanisms through the addition of linear springs and the use of length-adjustable links. The springs are used to constrain the mechanism and generate compliant behaviour, and the length-adjustable links are used to adjust the transmission ratio and modulate the apparent stiffness. The conditions for designing VSMs with symmetrical stiffness characteristics, capable of low-power cost stiffness modulation and decoupled control of equilibrium position and stiffness, are also derived. By selecting different spring-constrained joints, length-adjustable links, initial angles of input joints, and length ranges of the adjustable links, twelve energy-efficient VSMs with different stiffness performance are constructed. In addition, the concept design of a VSA that can vary its stiffness from zero to infinity is presented; this design uses only one linear torsion spring without a preload.